The AutoCAD programming and customizing quick references - Grabowski, Ralph (Autodesk Press, 1997)
The knowledge to program and customize AutoCAD Release 13 is here at your fingertips! Presenting clear and concise explanations, this quick reference features a one-command per page layout that's easy to use. Syntax, sample code, macro commands, and meta characters prepare users for their own programming sequences. Tap into the author's expertise to take full advantage of the programming and customizing capabilities of AutoCAD Release 13!